University of the Philippines computerized registration system over wireless application protocol - Uy, Jonel N (2000)
The objective of this paper is to develop a computerized registration system for the University of the Philippines based on wireless application protocol (WAP). Both client-side and server-side applications were developed. The client-side pages were mainly for user interface which were constructed with Wireless Markup Language (WML). Scripts were added to provide necessary logic in certain areas while server-side scripts were essential for the purpose of database connectivity. Structured Query Language (or SQL) was utilized for in-depth querying, manipulation and computing of the relational database. It is the so called "language of the relational database". The database consists of tables containing important records such as student information, class schedules, pins and web passwords. These information are then retrieved, modified, or edited depending on the system requirement. The Visual Basic Language/Script were also employed. All these are contained inside Active Server Pages (ASP) which the Web server recognizes and processes for internet publishing. From the WAP architectural point of view, any WAP-enabled phone can now access and interact with this internet based application instantly and easily.